2024
DOI: 10.1371/journal.pone.0294740
|View full text |Cite
|
Sign up to set email alerts
|

Trace element levels: How Substance Use Disorder (SUD) contributes to the alteration of urinary essential and toxic element levels

Borhan Mansouri,
Nammamali Azadi,
Arezo Hashemi Drebadami
et al.

Abstract: Increasing illicit drug use is one of the main problems in most countries or societies. Monitoring heavy metals and trace elements in this vulnerable group seems to be necessary. Therefore, we assessed the urinary trace element and toxic metals/metalloids concentrations (Zinc (Zn), Iron (Fe), Copper (Cu), Chromium (Cr), Lead (Pb), Cadmium (Cd), Arsenic (As), Nickel (Ni), and Mercury (Hg)) in opium, tramadol, and cannabis users compared to healthy subjects. In this cross-sectional study, patients with substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Similar to our findings, a recent study monitored urinary trace elements/heavy metals in individuals with substance use disorders (cannabis, opium, and tramadol). They found that these elements significantly increased in drug-dependent individuals compared to healthy individuals [27].…”
Section: Discussionmentioning
confidence: 98%
“…Similar to our findings, a recent study monitored urinary trace elements/heavy metals in individuals with substance use disorders (cannabis, opium, and tramadol). They found that these elements significantly increased in drug-dependent individuals compared to healthy individuals [27].…”
Section: Discussionmentioning
confidence: 98%